Pengaruh Sifat Fisik Tanah terhadap Hama Simphylid Pada tanaman Nanas (Ananas comosus (L.) Merr) di PT. Great Giant Pineapple Terbanggi Besar Lampung Tengah - Sandi Aji; Afandi Afandi; Lestari Wibowo; K.E.S. Manik (Jurnal Penelitian Pertanian Terapan, 2015)
This research was conducted in the planting area of pineapple (Ananas comosus) PT. GGP Terbanggi Besar Central Lampung indicated attacked by pests simphylid in March 2014 until May 2014. Analysis of soil physical properties carried out in the Laboratory of Soil Science, Department of Agrotechnology, Faculty of Agriculture, University of Lampung. The method used in this study is a survey method. Soil sampling conducted at three locations indicated simphylid pests. Soil sampling done at some point and some depth. Results from this research that pest symphilid most numerous in one location with a number of acquisition 172 tail where the location of the physical properties of good land which the density value of the content is low, the total pore low, macropores and high hardness low ground , allowing sinphylid be able to live and thrive. While at the location of two and three with the condition density value of the content is high, the total pore high, macropores low, and violence high soil pests simphylid not so much discovered as simphylid can not multiply and survive on the physical condition of poor soil Keywords: Pineapple, Symphilid, and physical properties of soil